Development of Gastro-floating drug delivery system by 3D Printing: Impact of formulation and design on the release profile of Baclofen - Abdulkhaleq, Nuha Mohammed; Ghareeb, Mowafaq M. (Journal of Contemporary Medical Sciences, 2022)
Objectives: Baclofen is a skeletal muscle relaxant with a short half-life and a narrow absorption window in the upper part of the gastrointestinal tract, and this study aims to formulate a sustained-release tablet of baclofen and 3D printing of gastro-floating device and study the effect of various polymers and device design on the release profile of baclofen. Method: Firstly, four formulas were produced through the hot-melt extrusion and direct compression of the extrudate to produce 30 mg baclofen tablets, then four gastro-floating devices (A, B, C, and D) were designed with two air pockets to enable the floating of the device and have drug-releasing windows with total surface area 4, 10, 20, and 40 mm2 respectively, for drug release. 3D printing of the devices was done by an FDM printer and the tablets were inserted into each device and test it for drug release. Results: Decreasing the surface area of the drug releasing windows revealed a significant reduction in the dissolution of baclofen irrespective of the type of polymers and useful for sustained release formulation but may be associated with lag time. Devices with one and two releasing windows (Device B and C respectively) sometimes revealed similar dissolution profiles and this related to the position of the window regarding the surface of the dissolution media. Device D with four windows and a 40 mm2 surface area was found to produce more reliable results. F3 which contains Eudragit RS-100 as the main polymer showed sustained release in device D where the complete dissolution of the drug occurred in 12 hours, and the gastro-floating device remained floating all the time and was assayed for drug content, FT-IR, and DSC study. Conclusion: Hot-melt extrusion was successfully employed to produce sustained release tablets of baclofen. FDM 3D printers are considered a potential tool to produce gastro-floating devices with the required design and release profile.